Employment, wages, and the economic cycle: differences between immigrants and natives - Christian Dustmann; Albrecht Glitz; Thorsten Vogel (Institute for the Study of Labor (IZA), 2009)
In this paper, we analyse differences in the cyclical pattern of employment and wages of immigrants and natives for two large immigrant receiving countries, Germany and the UK. We show that, despite large differences in their immigrant populations, there are similar and significant differences in cyclical responses between immigrants and natives in both countries, even conditional on education, age, and location. We decompose changes in outcomes into a secular trend and a business cycle component. We find significantly larger unemployment responses to economic shocks for low-skilled workers relative to high-skilled workers and for immigrants relative to natives within the same skill group. There is little evidence for differential wage responses to economic shocks. We offer three explanations for these findings: an equilibrium search model, where immigrants experience higher job separation rates, a model of dual labour markets, and differences in the complementarity of immigrants and natives to capital.
urn:nbn:de:101:1-200910141128
Keywords: E32; F22; J31; 330; Immigration; unemployment; business cycle; Konjunkturelle Arbeitslosigkeit; Lohndifferenzierung; Schock; Beschäftigungseffekt; Migranten; Ausländische Arbeitskräfte; Deutschland; Großbritannien